2003
DOI: 10.1046/j.1365-2745.2003.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

A test of the indirect facilitation model in a temperate hardwood forest of the northern French Alps

Abstract: Summary 1We tested the hypothesis that the more frequent occurrence of tree seedlings below the adult trees than in canopy openings might be explained by indirect facilitation. In a temperate hardwood forest, we compared the performance of five target tree seedlings ( Picea abies , Abies alba , Fagus sylvatica , Acer pseudoplatanus and Quercus petraea ), transplanted with or without a herbaceous competitor ( Molinia caerulea ), either within the forest or into experimentally created gaps. 2 We quantified chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 70 publications
4
41
2
Order By: Relevance
“…Secondly, since the PPFD was positively correlated with HL, the decrease of seedlings number with PPFD was interpreted by us as an effect of soil dryness. Alternatively, for some shade tolerant tree species, effect of indirect facilitation is observed, where seedlings are more abundant in shade due to competitive exclusion of herbs in better light condition (Pages andMichalet 2003, Filipiak et all 2005). However, in this study we did not observe any correlation between cover of forest floor vegetation and seedlings density.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, since the PPFD was positively correlated with HL, the decrease of seedlings number with PPFD was interpreted by us as an effect of soil dryness. Alternatively, for some shade tolerant tree species, effect of indirect facilitation is observed, where seedlings are more abundant in shade due to competitive exclusion of herbs in better light condition (Pages andMichalet 2003, Filipiak et all 2005). However, in this study we did not observe any correlation between cover of forest floor vegetation and seedlings density.…”
Section: Discussionmentioning
confidence: 99%
“…drier and warmer) than our high-productive study area. Page`s and Michalet (2003) found that the indirect positive effect of competition release for tree saplings by adult trees in a temperate hardwood forest was outweighed by the direct negative effect of light reduction. We suggest that microsites and resources (e.g.…”
Section: Coniferous and Deciduous Sapling Responses To Facilitationmentioning
confidence: 99%
“…Therefore to secure regeneration the forest manager has to adjust light availability by thinning to a degree that allows tree seedling to become established and grow, though not at the maximum rate, but still impedes the growth of competitive species [23]. This is known as indirect facilitation: the direct negative impact of shade on tree seedlings is lower than the direct positive effect of reducing competitive species growth [18]. Although the harmful role of competitive species on tree seedlings is well known [17], the literature does not offer much information on the precise response of competitive species to light in terms of growth and development.…”
Section: Introductionmentioning
confidence: 99%